Clinical validity of IntelliSpace Cognition digital assessment platform in mild cognitive impairment - Willem Huijbers; Nandor K. Pinter; Nandor K. Pinter; Mandy Spaltman; Mike Cornelis; Ben Schmand; Baraa Alnaji; Baraa Alnaji; Maxwell Yargeau; Sarah Harlock; Ryu Platinum Dorn; Ryu Platinum Dorn; et al. (Frontiers in Psychology)
We evaluated a digital cognitive assessment platform, Philips IntelliSpace Cognition, in a case-control study of patients diagnosed with mild cognitive impairment (MCI) and cognitively normal (CN) older adults. Performance on individual neuropsychological tests, cognitive z-scores, and Alzheimer's disease (AD)-specific composite scores was compared between the CN and MCI groups. These groups were matched for age, sex, and education. Performance on all but two neuropsychological tests was worse in the MCI group. After ranking the cognitive scores by effect size, we found that the memory score was the most impaired, followed by executive functioning. The Early AD/MCI Alzheimer's Cognitive Composite (EMACC) and Preclinical Alzheimer's Cognitive Composite (PACC) scores were constructed from the digital tests on Philips IntelliSpace Cognition. Both AD-specific composite scores showed greater sensitivity and specificity than the Mini-Mental State Examination or individual cognitive z-scores. Together, these results demonstrate the diagnostic value of Philips IntelliSpace Cognition in patients with MCI.